Hidden treasure - Cleland, Jane K. (Cleland, Jane K. Josie Prescott antiques mysteries., 2020)
"Josie Prescott's discovery of a mysterious antique trunk leads to a disappearance-and murder-in the next installment of this beloved cozy series set on the rugged New Hampshire coast, Jane K. Cleland's Hidden Treasure. Josie Prescott, owner of Prescott's Antiques & Auctions, and her new husband Ty have finally found their dream home-a Victorian beauty on the beach, known in the town of Rocky Point as "The Gingerbread House." It was recently vacated by Maudie Wilson, an aging widow, whose concerned nieces have moved her into a nearby assisted living facility. Josie befriends Maudie, who seems surprisingly sharp, considering her family's doubts about her soundness of mind. As Josie and Ty joyfully begin renovations on The Gingerbread House, the nieces report that Maudie, in her forgetfulness, may have left behind an old trunk, which she's desperate to get back. Sure enough, Josie finds the trunk inside a hidden dumbwaiter, and within it a jewel-encrusted box holding a sculpture of a cat. Josie can understand the sense of urgency about getting the objects back-they look valuable, and not just in the sentimental sense. But when Josie goes to return the box to Maudie, the woman has vanished. And on the floor of her empty apartment lies the body of someone bludgeoned to death. Sick with worry for Maudie's safety, Josie begins to piece together the clues to the murder. Everyone around her seems to want to pitch in, from Maudie's family, to the receptionist at the facility, to the young couple helping Josie with her renovations. But when the killer may be lurking nearby, Josie can't let her guard down around anyone"--